2006
DOI: 10.1159/000098054
|View full text |Cite
|
Sign up to set email alerts
|

Brain Lesions on MRI in Elderly Patients with Type 2 Diabetes Mellitus

Abstract: Background and Purpose: Diabetes mellitus (DM) type 2 has been associated with poor cognitive performance and dementia, particularly in elderly patients. The exact mechanisms underlying the cognitive dysfunction in DM remain unclear. Imaging studies of the brain could be helpful to give more insight into possible structural brain lesions underlying these cognitive dysfunctions. Therefore, we performed a study in independently living patients with DM type 2 in order to investigate the association between DM and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 42 publications
2
82
1
Order By: Relevance
“…However, diabetes has been associated with other brain changes, including white matter lesions [39] and the APOE ε4 allele has been associated with increased deposition of both Aβ plaques and neurofibrillary tangles [38,40]. Therefore, the decreased levels of cognitive function observed for the diabetic APOE ε4 carriers may be due to increased levels of vascular pathology in diabetic individuals and Aβ plaque deposition in APOE ε4 carriers.…”
Section: Discussionmentioning
confidence: 99%
“…However, diabetes has been associated with other brain changes, including white matter lesions [39] and the APOE ε4 allele has been associated with increased deposition of both Aβ plaques and neurofibrillary tangles [38,40]. Therefore, the decreased levels of cognitive function observed for the diabetic APOE ε4 carriers may be due to increased levels of vascular pathology in diabetic individuals and Aβ plaque deposition in APOE ε4 carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Several large population-based studies did not observe a significant association between T2DM and WMHs (reviewed in [53]). However, case-control studies that applied more refined WMH rating scales or volumetric measurements did observe a modest increase in WMH severity in patients with T2DM [54,58]. A recent study also identified T2DM is a risk factor for WMH progression [59].…”
Section: Brain Imaging In T2dmmentioning
confidence: 99%
“…Patients with T2DM show structural magnetic resonance imaging (MRI) changes (such as brain atrophy 10 and whitematter (WM) lesions 11 ) that are correlated with cognitive scores. 12 The MRI studies also report specific association between the hippocampal volume and glycated hemoglobin (HbA 1c ), a marker of long-term glucose control, and suggest that IR may be responsible for neuronal loss.…”
Section: Introductionmentioning
confidence: 99%